1998
DOI: 10.1093/ps/77.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and egg weight dynamics in layers

Abstract: The association between body weight-age and egg weight-age patterns was studied in a segregating population of laying hens belonging to the F3 generation of a Rhode Island Red x White Leghorn reciprocal cross. Body weight and egg weight were expressed as a function of time using the model developed by Weatherup and Foster. Each hen was characterized in terms of its asymptotic body weight (ABW), maturing rate for body weight (MBW), asymptotic egg weight (AEW), and maturing rate for egg weight (MEW) values. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…Feed conversion is also useful for measuring livestock productivity because feed conversion is a comparison between the ration consumed and the resulting weight gain. The higher the value of ration conversion indicates the more ration needed to increase body weight per unit weight and the lower the value of ration conversion means the quality of ration is getting better [14,15]. More and more a low conversion to ration, it means livestock is more efficient in using rations.…”
Section: Deuteronomy (G)mentioning
confidence: 99%
“…Feed conversion is also useful for measuring livestock productivity because feed conversion is a comparison between the ration consumed and the resulting weight gain. The higher the value of ration conversion indicates the more ration needed to increase body weight per unit weight and the lower the value of ration conversion means the quality of ration is getting better [14,15]. More and more a low conversion to ration, it means livestock is more efficient in using rations.…”
Section: Deuteronomy (G)mentioning
confidence: 99%
“…The maternal effects reduce as chicken are older (Barbieri et al, 2015;Maniatis et al, 2013;Norris & Ngambi, 2006). Another maternal effect, age of hen, may also affect BW because strong correlations between hen age and egg weight and strong correlations between egg weight and broiler BW especially at an early age were found (Di Masso, Dottavio, Canet, & Font, 1998;Tahir, Cervantes, Farmer, Shim, & Pesti, 2011;Whiting & Pesti, 1984). Failing to account for maternal effects results in reduced accuracy of selection, overestimated direct additive genetic effect and thus loss of selection response (Roehe & Kennedy, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies suggested that egg weight showed a curvilinear relationship with the increase of hen age (Di Masso et al, 1998;Suk and Park, 2001;Nangsuay et al, 2011;Tumova and Gous, 2012), and provided critical insights into controlling the increase rate of egg weight (Minvielle et al, 1994). However, these authors only evaluated the tendency and increment of egg weight between different weeks of age, lacking full evaluation of their genetic basis.…”
Section: Introductionmentioning
confidence: 99%